2021
DOI: 10.1021/acsenergylett.1c01126
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Molecular Doping and Energy Level Alignment Regulation for Perovskite Solar Cells with Efficiency Exceeding 23%

Abstract: Development of hole transport materials (HTMs) with comprehensive passivation effects and appropriate energy levels are urgently desirable for constructing highly efficient and stable perovskite solar cells (PSCs). Herein, we report an effective interfacial molecular doping strategy and energy level regulation approach to improve the performance of PSCs with ultrasimple carbazole-based HTMs CZ-As and CZ-Py. The pyridine-substituted HTM CZ-Py exhibits a stepped energy level with perovskite and CZ-As, effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 40 publications
1
80
0
Order By: Relevance
“…In order to evaluate the hole transport performance, we measured the hole mobility of the two HTMs using the space-charge-limited current (SCLC) model. 36 Fig. S11† shows the curves of the square root of the current density against voltage for PTAA and PFDTS.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the hole transport performance, we measured the hole mobility of the two HTMs using the space-charge-limited current (SCLC) model. 36 Fig. S11† shows the curves of the square root of the current density against voltage for PTAA and PFDTS.…”
Section: Resultsmentioning
confidence: 99%
“…Through this interaction, effective passivation of Pb 2+ defect can be obtained and the undesired charge recombination will be restricted. [ 28 ] It was also expected to influence the crystallization and morphology of the perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…An electrostatic potential (ESP) map of ZnPP was calculated by using Gaussview software with self-consistent field (SCF) density matrix and is presented in Figure 1b. It is clearly shown that the negative charges are mainly located on the N atom of the pyridine, which is expected to coordinate with Pb 2þ cations, [13,32] and the triphenylamine group is the electron-rich group conjugating with the electron-withdrawing group through the large delocalized π system supplied by the porphyrin. The UV-vis spectra and fluorescence emission spectra of ZnPP in chlorobenzene (CB) are shown in Figure S1a, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the stretching vibration of CN at 1567 cm −1 relative to pure ZnPP shifted downward to 1558 cm −1 in the mixture, indicating the coordinating interaction between the CN and the Pb 2+ in PbI 2 . [ 32 ] In addition, changes in the position of the other absorption peak, especially in the fingerprint area, were believed to be caused by the interaction between ZnPP and PbI 2 . And as X‐ray diffraction (XRD) patterns shown in Figure S2, Supporting Information, the peak at 2 θ of 12.7° (the (001) plane of PbI 2 ) of the mixtures of ZnPP and PbI 2 was strongly decreased compared to the pure PbI 2 .…”
Section: Resultsmentioning
confidence: 99%